Assessment of implant stability in immediate implant placement using different bone grafting materials: A clinical study - Mohammad Jalaluddin; Saurabh Sathe; Joyce Thomas; Shaista Haleem; Sachin Naik; Madhuniranjanswamy Mahalakshmamma Shivanna (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the present study was to assess the implant stability in immediate implant placement using different bone grafting materials. Materials and Methods: Twelve patients (5 males, 7 females, range of 40-58 years) were included in the study. All patients were divided into two groups based on the graft material used. For Group 1, Xenograft bone grafting material was used, and for Group 2, Freeze-dried bone allograft was used. The patients were suggested to rinse with 0.2% chlorhexidine mouth wash for 1 min. Periotome was used for atraumatic tooth extraction, and necessary care was taken to avoid fracture of socket wall. The implant was placed with respective bone grafting materials. An Orthopantomogram (OPG) radiograph is taken at the day of the operation to serve as baseline data for the marginal bone level. Clinical and radiological parameters were evaluated at baseline, 3 months, 6 months, and 12 months to assess the mean marginal bone level changes. Periotest was used for the measurement of implant stability. Results: The mean marginal bone level in Group 1 at baseline (13.58 ± 1.09), 3 months (12.64 ± 0.88), 6 months (12.02 ± 1.42), and 12 months (11.20 ± 1.26), respectively. In Group 2, the marginal bone level was at baseline (14.22 ± 0.26), 3 months (13.52 ± 1.28), 6 months (13.10 ± 0.32), and 12 months (12.12 ± 1.26), respectively. There was a statistically significant difference found in both the groups. Moreover, there was no statistically significant differences found between the groups at all the duration on intergroup comparison of the mean marginal bone level. The mean difference of implant stability in Group 1 the implant stability was 188.6 ± 22.5 and in Group 2 was 191.5 ± 18.2, and there was no statistically significant difference found between the groups. Conclusion: Both bone grafting materials used in the study showed improvement in implant stability and marginal bone levels after immediate placement of implant.